2006
DOI: 10.1111/j.1365-2249.2006.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the granzyme B inhibitor proteinase inhibitor 9 (PI-9) by activation of lymphocytes and monocytes in vitro and by Epstein–Barr virus and bacterial infection

Abstract: SummaryProteinase inhibitor 9 (PI-9) is an intracellular serpin expressed in lymphocytes and monocyte-derived cells. It is the only known endogenous natural antagonist of granzyme B (GrB), and its proposed function is protection of cells from misdirected GrB. We have studied the regulation of PI-9 in primary peripheral blood mononuclear cells (PBMCs) following ex-vivo stimulation, and in PBMCs from patients suffering from viral or bacterial infections. By intracellular flow cytometry, we found identical PI-9 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
(54 reference statements)
3
25
1
Order By: Relevance
“…Besides protecting the CTLs, PI-9 may also defend bystander cells or antigenpresenting cells likely to be exposed to GrB during an immune response. The expression of PI-9 in B cells (3), monocytes (23), mast cells (24), endothelial and mesothelial cells (25), smooth muscle cells (26) and dendritic cells (21,27) is consistent with such a role. Cells at immune-privileged sites including the eye lens capsula, testis, ovaries, placenta, embryonic stem cells also upregulate the PI-9 expression (20,25,28).…”
Section: Introductionsupporting
confidence: 57%
“…Besides protecting the CTLs, PI-9 may also defend bystander cells or antigenpresenting cells likely to be exposed to GrB during an immune response. The expression of PI-9 in B cells (3), monocytes (23), mast cells (24), endothelial and mesothelial cells (25), smooth muscle cells (26) and dendritic cells (21,27) is consistent with such a role. Cells at immune-privileged sites including the eye lens capsula, testis, ovaries, placenta, embryonic stem cells also upregulate the PI-9 expression (20,25,28).…”
Section: Introductionsupporting
confidence: 57%
“…1 AML cell line HL60 was exposed to each of the granzyme B constructs and we found that both the wildtype and mutant versions were cytotoxic with similar IC 50 values. Annexin V staining and caspase 3/7 assays confirmed the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio may be controlled or influenced by a number of immunomodulatory cytokines or infections that alter SERPINB9 expression. 21,[55][56][57] Selectivity of the SERPINB9-gzmB Interaction Granzyme B seems to be the sole protease target of SERPINB9. In a prime example of the importance of P1 residue in determining the specificity for protease inhibition, the SERPINB9 P1 residue is a glutamate, rather than the aspartate preferred by gzmB.…”
Section: Serpinb9 and Granzyme Bmentioning
confidence: 99%